Peran NGO dalam Tata Kelola Global: Keterlibatan Amnesty International dalam UN Summit for Refugee and Migrant 2016 - Wahyu Rozzaqi Ginanjar (Insignia: Journal of International Relations, 2020)
The refugee crisis is a global problem that needs serious attention. Responsibility-sharing is a core tenet of international responses to refugee crises. However, global governance, within the framework of the global refugee regime, is often practically ineffective to respond such problems. In this aspect, conceptual evaluation and reform are needed. In this particular momentum, civil society groups are able to be involved, in both performance evaluation and framework formulation related to global governance on refugees. One of the formal form of civil society is a non-governmental organization (NGO). Amnesty International is one of the NGOs involved in the process of evaluating and reforming global governance on refugees. This article aims to find out the form of Amnesty International's involvement in global governance on refugees. This study used descriptive-qualitative method. The findings in this article are that Amnesty International has a direct involvement in order to evaluate and to reform the global governance framework related to refugees through the 2016 UN High Summit for Refugee and Migrant. This involvement was demonstrated through performance evaluations and proposals for more genuine responsibility-sharing, both at the conceptual and technical level. Amnesty International in this involvement pursued an agenda that has two dimensions, namely: the dimension of institutional evolution and the agenda dimension.